Explaining experience curves for LNG liquefaction costs: Competition matter more than learning - Mads Greaker; Eirik Lund Sagen (Statistics Norway, Research Department, 2004)
In this paper we seek to identify different driving forces behind the fall in LNG liquefaction unit costs. Our focus is on organizational learning including process specific R&D, but we also seek to account for autonomous technological change, scale effects and the effects of upstream competition among liquefaction technology suppliers. To our surprise we find that upstream competition is by far the most important factor. This may have implications for the future development in costs as the effect of increased upstream competition is temporary and likely to weaken a lot sooner than effects from learning and technological change. On the other hand, the increased competition could also spur more innovation, and induce a new drop in future unit costs.
Keywords: O31; Q41; Q55; 330; Learning curves; Mark-up pricing; LNG costs